2014
DOI: 10.1515/bmc-2013-0036
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic regulations through DNA methylation and hydroxymethylation: clues for early pregnancy in decidualization

Abstract: DNA methylation at cytosines is an important epigenetic modification that participates in gene expression regulation without changing the original DNA sequence. With the rapid progress of high-throughput sequencing techniques, whole-genome distribution of methylated cytosines and their regulatory mechanism have been revealed gradually. This has allowed the uncovering of the critical roles played by DNA methylation in the maintenance of cell pluripotency, determination of cell fate during development, and in di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
21
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 80 publications
(155 reference statements)
1
21
0
Order By: Relevance
“…Current findings suggest that the conversion of 5-mC to 5-hmC is associated with demethylation processes [43][44][45], regulation of gene expression [46], and changes in the chromatin structure [47]. In this way, 5-hmC methylation could be an epigenetic mechanism participating in disease development, although these outcomes are still under investigation [44,48].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Current findings suggest that the conversion of 5-mC to 5-hmC is associated with demethylation processes [43][44][45], regulation of gene expression [46], and changes in the chromatin structure [47]. In this way, 5-hmC methylation could be an epigenetic mechanism participating in disease development, although these outcomes are still under investigation [44,48].…”
Section: Discussionmentioning
confidence: 97%
“…In this way, 5-hmC methylation could be an epigenetic mechanism participating in disease development, although these outcomes are still under investigation [44,48]. Due to the large presence of 5-hmC in the brain [49], several studies have been conducted in neurological diseases [50,51].…”
Section: Discussionmentioning
confidence: 99%
“…58 In general, the depletion of DNA methylation does not necessarily induce gene activation but rather renders a permissive state for activation. 59 Thus, it has been suggested that combined epigenetic marks, such as histone markers, chromatin state, and DNA methylation, might be better predictors for expression level than position of the CpG sites with respect to the gene. 57 A confounding factor in defining this relationship is the fact that assays based upon bisulfite conversion, such as Human-Methylation450 BeadChips, do not distinguish between 5hmC and 5mC.…”
Section: Discussionmentioning
confidence: 99%
“…55 5hmC is mostly depleted in CGIs, but found in the exons of gene bodies and highly enriched in distal regulatory elements, which include enhancers, insulators, p300-binding sites, and DHSs. [59][60][61] Thus, the observed enrichment of immune cell-specific DMGs in enhancer elements could at least in part include 5hmC sites. 59 Pathway analysis revealed similar biological pathways for negatively and positively correlated genes, indicating that the direction of correlation is not specific to a biological function.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation